RNA-Binding Proteins: A Role in Neurotoxicity? - Andrea Ocharán-Mercado; Jaqueline Loaeza-Loaeza; Yaneth Castro-Coronel; Leonor C. Acosta-Saavedra; Luisa C. Hernández-Kelly; Daniel Hernández-Sotelo; Arturo Ortega (Neurotoxicity Research, 2023)
Despite sustained efforts to treat neurodegenerative diseases, little is known at the molecular level to understand and generate novel therapeutic approaches for these malignancies. Therefore, it is not surprising that neurogenerative diseases are among the leading causes of death in the aged population. Neurons require sophisticated cellular mechanisms to maintain proper protein homeostasis. These cells are generally sensitive to loss of gene expression control at the post-transcriptional level. Post-translational control responds to signals that can arise from intracellular processes or environmental factors that can be regulated through RNA-binding proteins. These proteins recognize RNA through one or more RNA-binding domains and form ribonucleoproteins that are critically involved in the regulation of post-transcriptional processes from splicing to the regulation of association of the translation machinery allowing a relatively rapid and precise modulation of the transcriptome. Neurotoxicity is the result of the biological, chemical, or physical interaction of agents with an adverse effect on the structure and function of the central nervous system. The disruption of the proper levels or function of RBPs in neurons and glial cells triggers neurotoxic events that are linked to neurodegenerative diseases such as spinal muscular atrophy (SMA), amyotrophic lateral sclerosis (ALS), fragile X syndrome (FXS), and frontotemporal dementia (FTD) among many others. The connection between RBPs and neurodegenerative diseases opens a new landscape for potentially novel therapeutic targets for the intervention of these neurodegenerative pathologies. In this contribution, a summary of the recent findings of the molecular mechanisms involved in the plausible role of RBPs in RNA processing in neurodegenerative disease is discussed.

The 46359CT polymorphism of DNMT3B is associated with the risk of cervical cancer - Daniel Hernández-Sotelo; Rubén García-Aguilar; Yaneth Castro-Coronel; Jonathan J. Magaña; Marco Antonio Leyva-Vazquez; Luz del Carmen Alarcón-Romero; Esther López-Bayghen; Berenice Illades-Aguiar (Molecular Biology Reports, 2013)